Optical Character Recognition from Images - Angel; Jean Jisha .M; Vijayalakshmi Shivkhumar (International Journal of Engineering and Management Research, 2024)
Analysis of document images for information extraction has become very prominent in recent past. Wide variety of information, which has been conventionally stored on paper, is now being converted into electronic form for better storage and intelligent processing. This needs processing of documents using image analysis, processing methods. This article provides an overview of various methods used for digital image processing using three main components: Pre-processing, Feature extraction and the Classification. Pre-processing feature extraction and classification. Classification is an important step in Office Automation, Digital Libraries, and other document image analysis applications.